Peran Mindset Positif Terhadap Self Confidence Mahasiswa PAI Angkatan 2022 di IAIN Palangka Raya - Dwi Nurrahmi; Surawan Surawan (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Positive thinking plays a very important role in a person's self-confidence in their abilities. In this case, the positive mindset of PAI students is very important in determining the level of self-confidence of an individual. Therefore, this study aims to examine the role of positive mindset in shaping the self-confidence of students in the Islamic Education Study Program (PAI) class of 2022 at IAIN Palangka Raya. When facing academic, social, and personal pressures, many students experience a crisis of self-confidence. A positive mindset is believed to foster optimistic, resilient, and confident attitudes in facing challenges. This study uses a descriptive qualitative approach with in-depth interviews, observation, and documentation techniques. The results show that PAI students with a positive mindset can increase self-confidence, improve self-perception, reduce fear of failure, and provide stronger motivation for themselves. These findings reinforce the importance of mental coaching through positive thinking in supporting student character development.